"You are my slaves": a comparative study of the slavery metaphor in early rabbinic and early Christian parables - Stoutjesdijk, Martijn (Jewish and Christian perspectives series, 2025)
"Some of the slavery parables in the New Testament have been called "texts of terror," as the slaves who are portrayed in them are beaten or even cut in two. Despite - or because - their violence, slavery parables are often used in early Christian and early rabbinic literature to illustrate the unique relationship between God and his people. This study investigates the reasons for and meaning of using the master-slave metaphor in the parables: what does it tell us about early Christian and early rabbinic theology, including possibilities for critique and resistance vis-à-vis the divine, and what does it say about slavery in the ancient world?"--